The Effect of Education on Economic Growth : Case of Russia and Kazakhstan in a modern history - Bissapin, Alikhan (2024)
This thesis delves into the intricate connection between education and economic growth, with a specific focus on Russia and Kazakhstan. The primary goal is to examine both theoretically and empirically whether the unique educational bases in these countries, influenced by factors such as enrolment rates, educational expenditure, and literacy levels, etc, demonstrate a relationship with economic development, as suggested by existing literature (Ozturk 2008, , Benos and Zotou 2014, etc). The central hypothesis tests for a positive correlation between education levels and economic development in both nations from 1991 to 2022. While not the inaugural study in this region (Mihr 2020), this thesis contributes to the broader discussion on the role of education in economic development by focusing on specific determinants. It aims to provide valuable insights for policymakers in Russia, Kazakhstan, and other countries aiming to enhance economic growth through educational investments. The thesis consists of two main sections: a theoretical part and an empirical one. The theoretical section endeavours to establish a comprehension of the subject by exploring existing literature, theoretical frameworks, and the mechanisms through which education contributes to economic growth. It underscores the significance of the topic within the context of modern history, relying on historical facts and policy analysis. The empirical section entails gathering relevant data, encompassing education indicators, information on economic growth, and control variables for both Russia and Kazakhstan. This data, spanning the period from 1991 to 2022, enables the testing of the main hypothesis through regression analysis. The findings aim to serve as substantiation supporting insights for policymaking.